The histone deacetylase sirtuin 2 is a new player in the regulation of platelet function. (11th June 2015) - Moscardó, A.; Vallés, J.; Latorre, A.; Jover, R.; Santos, M. T.
Summary Background Histone deacetylases (HDACs) play a key role in signaling in many cell types. However, little is known about the participation of HDACs, particularly sirtuins (SIRTs), in platelet reactivity. Objective To investigate the role of HDACs in platelets, we examined the effects of SIRT inhibition on platelet function and protein acetylation in human platelets. Methods We used washed platelets obtained from healthy subjects. Cambinol (SIRT1 and SIRT2 inhibitor), AGK2 (specific SIRT2 inhibitor) and EX527 (specific SIRT1 inhibitor) were used as SIRT inhibitors. Platelets were stimulated with collagen, thrombin, or U46619, and platelet responses were determined according to optical aggregometry findings, dense granule release, and cytosolic calcium levels (Fura‐2AM fluorescence). Protein acetylation and phosphorylation were assessed by immunoblotting. Results SIRT inhibition remarkably reduced platelet responses (aggregation, granule release, and cytosolic calcium level; P < 0.05). SIRT2 was present in platelets at the level of mRNA and protein, and its specific inhibition reduced platelet responses. The acetylated protein pattern observed in resting platelets changed during platelet aggregation. Inhibition of SIRT2 increased the acetylation of Akt kinase, which in turn blocked agonist‐induced Akt phosphorylation and glycogen synthase kinase‐3β phosphorylation, which are markers of Akt activity. Finally, collagen‐induced aggregation provoked Akt acetylation. Conclusions Regulation of protein acetylation by SIRT2 plays a central role in platelet function. The effects of SIRT2 are mediated in part by the acetylation and inhibition of Akt. These results open a new avenue for research into the control of platelet function, and may help to identify new therapeutic targets.